1990
DOI: 10.1161/01.hyp.15.6.643
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular relaxation of diabetic spontaneously hypertensive rat.

Abstract: Diabetes, and possibly the hypothyroidism that attends diabetes, impairs mechanical relaxation of ventricular muscle, in part by depressing the rate of Ca 2+ uptake by sarcoplasmic reticulum. Left ventricular hypertrophy exacerbates the adverse effects of diabetes on cardiac performance, but its effects on relaxation variables have not been well characterized. We examined the impact of streptozotocin-induced diabetes (8 weeks) on ventricular pressure load-dependent relaxation and sarcoplasmic reticular calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
6
7
0
Order By: Relevance
“…Insulin treatment, in spite of increased serum insulin, also did not reduce hyperglycemia in diabetic SHR [21]. The significantly reduced body weight observed in control SHR is similar to what was reported by other researchers [21]. Our results also showed that in STZ-induced diabetes, the magnitudes of weight loss were more in diabetic SHR than in diabetic WKY.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Insulin treatment, in spite of increased serum insulin, also did not reduce hyperglycemia in diabetic SHR [21]. The significantly reduced body weight observed in control SHR is similar to what was reported by other researchers [21]. Our results also showed that in STZ-induced diabetes, the magnitudes of weight loss were more in diabetic SHR than in diabetic WKY.…”
Section: Resultssupporting
confidence: 91%
“…This might be due to the severity of hyperglycemia or diabetes in these rats. Insulin treatment, in spite of increased serum insulin, also did not reduce hyperglycemia in diabetic SHR [21]. The significantly reduced body weight observed in control SHR is similar to what was reported by other researchers [21].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Characteristics of abnormal function include prolonged duration and reduced rate of contraction and relaxation, as measured in whole hearts (5,13), isolated papillary muscle (20,43), and isolated ventricular myocytes under chemically induced and genetically predisposed diabetes (35,36). Similar to our earlier observations, the present study demonstrated prolonged TPS and Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we reported that STZ-induced diabetes mellitus caused reduced SBP in SHR [12]. This hypotensive effect of diabetes on elevated blood pressure was also reported by other authors [2224]. Besides, our study indicated that short-term (3 weeks) administration of Malaysian tualang honey in STZ-induced diabetic SHR resulted in further reduction in SBP [12].…”
Section: Introductionsupporting
confidence: 83%